THE ANALYSIS OF THE SOLAR X-RAY FLARE ON NOVEMBER 2, 1992 - L. N. Dzhimbeeva; G. A. Mankaeva; A. Y. Yazlyeva; C. S. Akmyradova; A. M. Maksatmyradova (Современная наука и инновации)
The Yohkoh space solar observatory has been designed to take images of the Sun in the soft X-ray range (10A), with particle energies of ~1 keV. A coronal loop flare occurred on November 2, 1992, which was captured by Yohkoh, which made it possible to record the first time that the top of the coronal loop was periodically pulled up and then closed again. This process is very similar to the way the tail of the Earth's magnetosphere is pulled out during a magnetic substorm. It was also possible to trace the evolution of the loop during a powerful flare.